THE IMPLEMETATION OF SCIENTIFIC APPROACH IN THE TEACHING WRITING RECOUNT TEXT AT THE FIRST GRADE STUDENTS OF SMA NEGERI 1 PARE - Sulistyowati, Sri (LENTERA : Jurnal Pendidikan dan Pengajaran, 2019)
This research is to describe the implementation of scientific approach in the teaching writing recount text at the first grade students of SMA Negeri 1 Pare. This research design used the descriptive qualitative. The analysis data has three steps: data reduction, data display, and verification, Miles and Huberman (1994). The object of this data is the implementation of scientific approach in the teaching writing recount text at the first grade students of SMA Negeri 1 Pare. This research is conducted by three research methods: observation, interview, and documentation. This research has five results: (1) the planning of scientific approach in the teaching writing recount text at first grade students of SMA Negeri 1 Pare, (2) the implementation of scientific approach in the teaching writing recount text, (3) the evaluation of scientific approach in the teaching writing recount text, (4) the result of students’ writing in writing recount text by using scientific approach, and (5) the students’ perception on the implementation of scientific approach.